Somewhere between fiction and non-fiction New approaches to writing crime histories - Haebich, Anna (Text Journal, 2015)
This paper explores innovative ways of writing across the borders between fiction and non-fiction in crime histories and examines how crime sources can actively encourage writing that is imaginative, subjective and ambiguous. Drawing on recent historiographic critiques of the archive, the paper argues that the constructedness of archival crime sources and close responsive reading and interpretation of these sources can validate, even demand, of historians the use of nuanced fictive writing practices that eloquently express the complexity of the crimes, the killers, the victims, the societies that created them and the intricacies and truths of the sources that contained them. As well as iconic examples from the literature, the paper examines my own research and writing about two very different murder trials from Perth, Western Australia, one already published, the other a work in progress. The trials of Martha Rendell and Audrey Jacob bookend sixteen years of Perth history from 1909 to 1925 when expectations and representations of women’s gender roles in Perth changed dramatically, producing very different outcomes for the women. The archival sources for each case determine the contrastive structures and styles for developing the resulting works of scholarly crime prose fiction.